Quentin Blake's ABC - Blake, Quentin 1932- (Red Fox, 2012)
Rhyming text and illustrations depict objects for each letter of the alphabet, from apples and breakfast in bed to a hairy yak and plenty of zippers
Originally published: London: Jonathan Cape, 1989
Keywords: English language / Alphabet / Pictorial works / Juvenile literature; Alphabet rhymes; Alphabet; English language / Alphabet; Englisch; Bilderbuch